A elação entre linguagem e ontologia no crátilo de Platão - Santos, Joedson Silva dos (2019)
This project is thematically limited to the analysis of the relationship between language and ontology from the platonic dialogue: Cratylus. In this dialogue, the relationship between language and ontology implies an epistemology, and the articulation between language and epistemology presupposes a stable and objective reality. Both Plato and some pre-socratic and sophists inaugurated a series of reflections around the physis/nomoi antinomy, based on the two opposing paths in vogue at the time: naturalism and conventionalism. Starting from the debate between Socrates and his interlocutors, Hermogenes and Cratylus, a problem emerges, namely, the justness, correction or accuracy of the name (orthotes onomaton) in relation to the thing (onta). For Hermogenes this relationship is conventional, that is, there is no natural correspondence between the name and the thing, in this sense, language is separated from reality. For Cratylus it is natural, because the name and the thing are connected in such a way that to say something is to say the thing, so that the being and the language are inseparable. Between the extreme of the two theses is Plato's position of maintaining a balance between language and reality, through the separation of language from reality without losing the direct relationship with it. For the purposes of the dissertation, we will examine how the relationship between language and ontology implies in Socrates' epistemology, as well as the Cratilian epistemic refutation promoted by him.